Beyond The ‘Like’: The Influence of Social Media Algorithms on the Formation of Social Movements and Collective Identity - Liam Taylor; Olivia Williams; Benjamin Carter (Journal of Social Science Utilizing Technology, 2025)
Background. Social media platforms have become a pivotal force in shaping modern social movements, with algorithms playing a significant role in influencing collective behavior and identity. This research investigates the impact of social media algorithms on the formation of social movements and the construction of collective identity. Purpose. The study explores how algorithmic content curation, such as personalized recommendations and engagement-driven metrics, affect users' perceptions and participation in social movements. The primary objective is to analyze how these algorithms enhance or hinder the visibility of movements and influence individuals' alignment with collective causes. Method. A mixed-methods approach is employed, combining quantitative analysis of social media data with qualitative interviews to understand user experiences and motivations. Results. The findings indicate that social media algorithms both empower and constrain social movements by amplifying certain narratives while marginalizing others. The study also reveals that algorithms contribute to the creation of echo chambers, reinforcing group identities but also limiting exposure to diverse perspectives Conclusion. . In conclusion, while social media algorithms provide a platform for social mobilization, they also present challenges related to inclusivity and diverse representation. The research highlights the dual nature of algorithmic influence and calls for a more ethical approach to algorithm design to foster democratic participation in online movements.